Impact response of an origami-shaped composite crash box: Experimental analysis and numerical optimization. (15th January 2021) - Ciampaglia, A.; Fiumarella, D.; Boursier Niutta, C.; Ciardiello, R.; Belingardi, G.
Abstract: In this work, an investigation of the crush response of a simplified CFRP origami crash box subjected to axial impact is proposed. Crash boxes are thin-walled structural components of the vehicles designed to absorb energy during impact events at low-medium velocity. In particular, the crash boxes must guarantee a progressive and controlled energy absorption, avoiding peak of force (and thus acceleration) that can lead to passenger injury. In recent years, crash boxes made of carbon fibre reinforced polymer (CFRP) have found application in the automotive sector. However, their brittle failure mode leads to an irregular crushing trend characterized by peak of force. Thereafter, the crushing behaviour of the composite material structures can be improved by modifying their geometrical parameters. Among the most promising solutions, the origami structure is increasingly considered for crash boxes. The origami crash box here considered consists of four axially stacked basic structures. Each basic structure is composed of four trapezoidal faces and four triangular faces. The upper cross section is squared, whereas the lower cross section has an octagonal shape. The structural behaviour of the origami component was investigated according to different sizes of the triangular faces. The numerical models were simulated with the finite element commercial code LS-Dyna in its explicit formulation. The optimal shape of the origami structure in terms of maximum energy absorption and limited force peak was defined in LS-OPT environment. The objective function of the shape optimization algorithm was set to maximize the energy absorption, while limiting the peak of force. The optimal shape defined presented larger sizes in the top basic structures than in the bottom parts, resulting in more inclined faces. The result suggested that more inclined faces in the top part can guarantee a fracture-triggering effect in the crash box, which ensured a smaller peak force.